Hicks's Contribution To Keynesian Economics - Coddington, Alan (Journal of Economic Literature, 2016)
PHE PURPOSE OF this paper is to examine Hicks's contribution to macroeconomic theory in those respects in which it constitutes a response to, or a development of, the work of John Maynard Keynes. Thus, while it is narrower in scope than an attempt to assess Hicks's contribution to macroeconomic theory, it is broader in scope than an attempt to see Hicks as Keynes's interpreter: for an interpreter is judged only by the faithfulness with which he translates the material given to him; he is not required to extend, recast, criticize, or reconstruct that material. We shall be concerned, then, with what Hicks got out of Keynes's writings and what he did with it; not with what was really there. I therefore shall not be concerned with the authenticity or doctrinal purity of Hicks's Keynesianism. In considering Hicks's contribution to I shall be concerned with two distinct but related matters. First, I shall be concerned, in Sections II and III, with Hicks's response to-and in particular his criticisms of-what himself actually wrote. Also, however, I shall, in Section IV, be concerned with Hicks's contribution to those ideas that eventually entered the public domain as economics, quite irrespective of whether those ideas accurately reflect what may or may not have had in mind at some crucial juncture of his career. I should emphasize that these two concerns are intended to consist simply of a narrower and a broader one: they do not involve a contrast between a profound and intellectually challenging of Keynes on the one hand, to be set against a vulgar and degenerate Economics on the other. Accordingly, I shall be using the term Keynesian in a robust sense; I use it in full recognition of the possibility of diverse shades of opinion, and of extreme or borderline cases, on the understanding that it is what all these have in common that is important.